La Gestión Administrativa y el Liderazgo en Época de COVID 19 en la empresa GR Tecnología. - Rosero Obando, Gerardo Rodrigo (2023)
The research called Administrative Management and Leadership in Times of COVID-19 in the GR Technology Company establishes the purpose of analyzing the current reality of the company in the administrative field, especially after the pandemic caused by the SARS-CoV2 virus. COVID-19 has impacted most companies, in addition to establishing the existing relationship between the current administrative management and the leadership that has been maintained in it. Initially, a situational diagnosis of the executive management was established by collecting information within the GR technology company. Thus, various knowledge was also delimited at a theoretical level with bibliographic support. The leadership variable, for its part, was evaluated with data provided by employees of the same company. From the above, the research was proposed by an exploratory and descriptive type since the variables under study were previously analyzed in a limited manner. With the results obtained, several administrative management strategies were established that allow the improvement of leadership. For this purpose, a survey of the staff and an interview with the company manager to know the way in which the variables are related together and individually. Finally, the strategies above were delimited, in addition to evidencing the existence of an incidence between the administrative management and the leadership presented by the company GR TECNOLOGÍA in times of COVID-19.